2022
DOI: 10.3390/biomimetics8010009
|View full text |Cite
|
Sign up to set email alerts
|

Urban Biomimicry for Flood Mitigation Using an Ecosystem Service Assessment Tool in Central Wellington, New Zealand

Abstract: Many cities are vulnerable to flooding due to their high proportion of impervious surfaces and lack of vegetated land cover. This vulnerability will often be exacerbated by changing rainfall and storm patterns due to climate change. Using the principles of urban biomimicry, this study aims to show an ecosystem service-based approach to designing an urban green infrastructure network for stormwater management in densely built areas that more closely emulates natural hydrology processes. Nature Braid (next-gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…In landscape ecology, ecological networks are primarily designed to connect and protect increasingly fragmented ecosystems. In related research fields in global regions, other terms are conceptualized similar to ecological networks, such as ecological infrastructure (EI) and green infrastructure (GI) (Louis-Lucas et al, 2022; MacKinnon et al, 2022; Thomas et al, 2022). These concepts used by landscape ecologists and planners refer to a natural life-support system that connects fragmented landscapes in cities and sustains natural ecological processes (Benedict and McMahon, 2002; Bryant, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…In landscape ecology, ecological networks are primarily designed to connect and protect increasingly fragmented ecosystems. In related research fields in global regions, other terms are conceptualized similar to ecological networks, such as ecological infrastructure (EI) and green infrastructure (GI) (Louis-Lucas et al, 2022; MacKinnon et al, 2022; Thomas et al, 2022). These concepts used by landscape ecologists and planners refer to a natural life-support system that connects fragmented landscapes in cities and sustains natural ecological processes (Benedict and McMahon, 2002; Bryant, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…This type of flooding is usually local and can cause significant damage in urban areas, especially if the drainage system is inadequate or overwhelmed [10,11]. Due to unsustainable land management practices coupled with climate change, floods have become more frequent and severe at a global level over the past few decades [12][13][14], and the problem is exacerbated in the built environment as impervious surfaces of urban areas reduce adaptation to flooding that is otherwise provided by vegetation and soil [8,12]. At the same time, we are observing exponential urbanization [15], which, amongst other things, will further intensify land-use transformation, potentially turning even more green areas into urban built-up land [5].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Their results showed that proper implementation of permeable pavements reduced the flow of surface runoff by between 44 and 92%. Numerous studies focusing on green infrastructure implementation to mitigate the impacts of flooding have been conducted [21][22][23][24][25][26]. However, it is essential to recognize that although Low Impact Development (LID) systems can effectively manage stormwater, their efficacy could be constrained during heavy rainfall events.…”
Section: Introductionmentioning
confidence: 99%